Dampak Covid-19 Terhadap Pelaksanaan Pembelajaran PJOK Di Madrasah Se-Kabuoaten Kediri - Rizky Septyan Karya Utama; Nanik Indahwati (Efektor, 2022)
This study aims to determine the impact of COVID-19 on physical education and sports learning at the Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah public and private levels in the Kediri Regency. This study uses a qualitative descriptive method. The population in the study is all physical education and sports teachers, totalling 284 under the auspices of the Ministry of Religion of Kediri Regency. The data will be revealed using an instrument in the form of a validated questionnaire. Based on the results of data analysis using SPSS 12 that in the Kediri Regency, most of the Physical Education and Sports and Health teachers are constrained in carrying out online learning because of the Covid-19 pandemic. Some of the factors that become obstacles and obstacles in carrying out and providing evaluations are due to several factors, including because online learning is a new learning method for students and teachers, considering that so far, teachers have implemented physical learning face to face with students. In addition, the constraints of quota costs and the use of mobile phones in the same family that is used together also make students feel burdened. This study indicates that the learning of Physical Education, Sports, and Health in Madrasahs throughout Kediri Regency has had a significant impact due to the Covid-19 pandemic 19, especially in terms of the implementation of learning. So teachers are required to use online or online learning with Android and can make home visits to check students' health